2022
DOI: 10.1186/s12894-022-01148-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel autophagy-related long non-coding RNAs prognostic risk score for clear cell renal cell carcinoma

Abstract: Background As the main histological subtype of renal cell carcinoma, clear cell renal cell carcinoma (ccRCC) places a heavy burden on health worldwide. Autophagy-related long non-coding RNAs (ARlncRs) have shown tremendous potential as prognostic signatures in several studies, but the relationship between them and ccRCC still has to be demonstrated. Methods The RNA-sequencing and clinical characteristics of 483 ccRCC patients were downloaded downlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In recent years, an increasing number of studies have shown that IKBIP can serve as a predictive biomarker for many cancers, such as glioma [12,13], renal cell carcinoma [14] and gastrointestinal cancer [26]. However, whether IKBIP can be used as a biomarker for ESCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have shown that IKBIP can serve as a predictive biomarker for many cancers, such as glioma [12,13], renal cell carcinoma [14] and gastrointestinal cancer [26]. However, whether IKBIP can be used as a biomarker for ESCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IKBIP has been reported to maintain the abnormal proliferation of glioblastoma cells by inhibiting the degradation of CDK4 [12]. Importantly, a growing number of studies have shown that IKBIP may serve as a predictive biomarker and a potential therapeutic target for several cancers, such as glioblastoma [13], renal cancer [14] and lung cancer [15]. However, the role of IKBIP in ESCC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…), or did not thoroughly established potentially significant treatments that could be used to treat the different risk groups of patients their model could stratify. For instance, Tang et al established a prognostic model on 9 autophagy-related long non-coding RNA 42 , Xu et al constructed a panel of 10 cuproptosis-associated lncRNAs 43 , Ming et al designed a panel comprising 12 N7-Methylguanosine (m7G)-related long non-coding RNAs (lncRNAs) 44 , Sun et al constructed a ferroptosis-related prognostic signature based on 19 ferroptosis-related genes 45 , Liu et al identified a 13-gene risk signature related to ccRCC patients' metabolism 46 , Zhao et al described their finding on 3 metabolic genes that were used to build a risk score model 47 , and Peng et al proposed a 3-gene methylation signature that could be used as a risk stratification tool to predict patient's outcomes and treatment response 48 . Compared these previous literature, to our existing knowledge, this is the first study to thoroughly investigate a panel of 13 proteins in ccRCC based on which we established an algorithm able to differentiate high-risk from low-risk patients, predict their 1-, 3- and 5-year OS, perform immune-related functional analysis to investigate the potential effect of immunotherapeutics in these 2 groups of patients and screen for potential drugs that could have be effective in the high and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%